Health-related quality of life in women with primary ovarian insufficiency: a scoping review of the literature and implications for targeted interventions. Issue 12 (14th September 2022) - McDonald, Isabella R; Welt, Corrine K; Dwyer, Andrew A
Abstract: STUDY QUESTION: What is known about health-related quality of life (HR-QoL) in women with idiopathic primary ovarian insufficiency (POI)? SUMMARY ANSWER: Women with POI have a range of unmet psychosocial needs relating to three interrelated themes: 'diagnostic odyssey', 'isolation and stigma' and impaired 'ego integrity'. WHAT IS KNOWN ALREADY: Prior studies have reported increased depressive symptoms, diminished sexual function and altered body image/self-concept in women with POI. STUDY DESIGN, SIZE, DURATION: A systematic scoping review (11 databases) on HR-QoL in POI including published quantitative, qualitative and mixed-methods studies as well as unpublished gray literature (i.e. unpublished dissertations) through June, 2021. PARTICIPANTS/MATERIALS, SETTING, METHODS: After removing duplicates, 1244 articles underwent title and abstract review by independent reviewers. The remaining 72 relevant articles underwent dual full text review to determine inclusion criteria yielding 24 articles (100% concordance) for data extraction. Findings were summarized in tables by methodology and recurrent HR-QoL themes/sub-themes were mapped to define key aspects of HR-QoL in POI. Promoters of active coping were charted at the individual, interpersonal and healthcare system levels. Targets for tailored interventions supporting active coping and improved HR-QoL were mapped to the Theory of Planned Behavior (TPB). MAIN RESULTS AND THE ROLE OF CHANCE: Three interrelated themes affecting HR-QoL in POI emerged from the data synthesis. First, the theme 'diagnostic odyssey' comprised sub-themes of uncertainty, lack of control, knowledge gaps, discontinuous care and negative clinical interactions. The second theme 'isolation and stigma' included sub-themes of guilt, shame, concealment, feeling labeled as infertile, lack of social support and unsympathetic clinicians. The third theme, impaired 'ego integrity' captured sub-themes of decreased sexual function, altered body image, psychological vulnerability and catastrophizing. Targets promoting active coping at the individual (n = 2), interpersonal (n = 1) and healthcare system (n = 1) levels were mapped to the TPB to inform development of tailored interventions supporting active coping and improved HR-QoL in POI (i.e. narrative intervention, co-creating patient-facing materials, peer-to-peer support and provider resources). LIMITATIONS, REASONS FOR CAUTION: No studies using a POI-specific HR-QoL instrument were identified. No interventional studies aimed at improving HR-QoL in POI were identified. Only articles published in English were included in the study. WIDER IMPLICATIONS OF THE FINDINGS: Women with POI frequently have impaired HR-QoL related to the life-altering infertility diagnosis. The range of unmet psychosocial needs may be relevant for informing interventions for other populations with infertility. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the Eunice Kennedy Shriver National Institute of Child Health and Human Development 'Massachusetts General Hospital—Harvard Center for Reproductive Medicine' (1 P50 HD104224-01 NICHD). The authors have no conflicts to declare. REGISTRATION NUMBER: N/A.